Antanas Smetona and his Lithuania : from the national liberation movement to an authoritarian regime (1893-1940) - Eidintas, A. (Alfonsas) (On the boundary of two worlds, 2015)
This biographical overview of the life of Antanas Smetona (1874-1944), his importance in the Lithuanian national movement, his central role in the emergence of modern Lithuania (1918-1920), and the development of the various groups of nationalists in Lithuania, offers a picture of the creation of a national state in XXth century Europe. Twice the president of Lithuania (1919-20 and 1926-40), the authoritarian ruler of the state from 1926-1940, Smetona established his role as a capable and needed politician in Lithuania¿́¿s political life, a middle person between the political left and right. The study characterizes Smetona¿́¿s closest and most important associates, who helped him to formulate legislation for his model of presidential regime, the nationalistic ideology, and the development of national economy. Despite its authoritarian tendencies Smetona¿́¿s rule surprisingly continued to be for many Lithuanians a symbol of Lithuanian independence and national freedom through the years of Soviet occupation.